SATYBALDY NAMATOV WAS AN INNOVATIVE METHODOLOGIST OF HIS TIME - Melisova A. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The education system has always played an important role in the development of society. Teachers and methodologists are the backbone of this system. Their role in the educational process is of special significance, as they develop various teaching methods and introduce teachers and students to advanced practices in education. In the early years of Soviet power in Kyrgyzstan and other Soviet republics, illiteracy was a serious problem, and a large part of the population could neither read nor write. This, in turn, created significant obstacles to the social and economic development of society. Satybaldy Namatov was one of the people who strove to address this issue. He made a significant contribution to the literacy of the Kyrgyz people, the development of high-quality textbooks that met the demands of the time, and, most importantly, the establishment of Kyrgyz language teaching methodology as a separate science. He was a highly educated educator of his time. His life journey, educational activities, and the rich pedagogical and methodological legacy he left behind deserve comprehensive study. In our brief article, we have attempted, even if only to a small extent, to highlight his innovative qualities and some of his works, which remain relevant to this day.